Student Management Practices for Strengthening Academic and Non-Academic Achievement at SMP Negeri 30 Medan - Candra Ronitua Gultom (Yayasan Pustaka Karya Mandiri, 2026)
Student management plays an important role in helping schools identify student potential, organize development programs, strengthen discipline, provide academic and non-academic guidance, and evaluate achievement outcomes. This study aimed to describe student management practices in improving students’ academic and non-academic achievement at SMP Negeri 30 Medan. The study employed a descriptive qualitative approach. The informants consisted of the principal, vice principal of student affairs, academic coach, extracurricular coach, homeroom teacher, academically achieving student, and non-academically achieving student. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings showed that student management at SMP Negeri 30 Medan was implemented through planning, organizing, academic development, non-academic development, discipline strengthening, monitoring, evaluation, and follow-up. The school prepared student programs based on student needs, school activity calendars, interest and talent mapping, and achievement targets. Academic development was implemented through tutoring, enrichment, remedial activities, olympiad preparation, and teacher mentoring. Non-academic development was implemented through extracurricular activities, competition preparation, intensive training, and coaching in sports, arts, scouting, religious activities, and literacy. Achievement data showed a positive trend from 2021/2022 to 2024/2025. The average academic score increased from 78.40 to 83.75, academic achievements increased from 4 to 11, non-academic achievements increased from 7 to 20, and student participation in competitions increased from 20 to 43 students. The supporting factors included principal commitment, student affairs coordination, teacher coaching, student motivation, parent support, and school culture. The inhibiting factors included limited training time, unequal student motivation, limited facilities in certain fields, dense activity schedules, and non-integrated achievement documentation. The study concludes that student management strengthens achievement when it is implemented through systematic planning, potential mapping, structured coaching, discipline development, monitoring, evaluation, and collaboration with parents.